Jesús Campos’ Playwriting and the Andalusian Legacy. Reflection on the Exchange of two Cultures through La Cabeza del Diablo - Salem, Khaled (Anaquel de Estudios Árabes, 2007)
Jesús Campos García, the author of La Cabeza del diablo, devotes his creative effort to recover the historical elements which were crucial in defining the present-day Europe, and the cultural exchange between both sides of the Mediterranean Sea. This play is imbued with Al-Andalus Arabic cultural essences to explain how they were brought into Europe. It’s a well-documented fiction play which shows the contact between the two main cultures at that time: Arabic and Christian, with an important Jewish presence. La Cabeza del Diablo is the head of wisdom, the man with a bird’s head, a reference to the Egyptian god Thoth. But at the end it is related to dreams, madness, the hero Gerberto’s thirst for power. In order to understand this play we must place it in the context of the present-day scenario, we must translate it into the contemporary expression of the facts and feelings raised in the play